A near-isothermal expander for isothermal compressed air energy storage system. (1st September 2018) - Zhang, Xinjing; Xu, Yujie; Zhou, Xuezhi; Zhang, Yi; Li, Wen; Zuo, Zhitao; Guo, Huan; Huang, Ye; Chen, Haisheng
Highlights: A specific expander was analysed by theoretical and experimental methods. A quasi-isothermal expansion process was further improved by spraying water into the cylinder. Specific work generation was enhanced and the cylinder size was reduced. Abstract: Compressed air energy storage technology is considered as a promising method to improve the reliability and efficiency of the electricity transmission and distribution, especially with high penetration of renewable energy. Being a vital component, the expander takes an important role in compressed air energy storage operation. The specific work of an expander can be improved through an isothermal expansion compared with the adiabatic expansion process due to a nearly constant temperature which enables the expander to operate with a high pressure ratio. In this study, a specific reciprocating expander with a high pressure ratio was developed and its adiabatic expansion characteristics were measured. Numerical modelling was performed to simulate adiabatic expansion. This model was also validated by experimental results. Based on these findings, we propose a quasi-isothermal expansion process using water injection into the expander cylinder. Modelling was also extended to simulate the quasi-isothermal process by introducing water–air direct heat transfer equations. Simulation results showed that when spraying tiny water droplets into the cylinder, the specific work generated was improved by 15.7% compared with that of the adiabatic expansion under the same air mass flowrate, whilst the temperature difference was only about 10% of that of the adiabatic process, and cylinder height was decreased by 8.7%. The influence of water/air mass flowrate ratio and the inlet temperature on the expander performance was also studied.